The complete chloroplast genome of Tainia dunnii (Orchidaceae): genome structure and evolution. Issue 1 (2nd January 2020) - Xie, Tai-Xiang; Yu, Xia; Zheng, Qing-Dong; Ma, Shan-Hu; Liu, Zhong-Jian; Ai, Ye
Abstract: Tainia dunnii is a terrestrial orchid with high ornamental value. Herein, we assembled the complete chloroplast genome of Tainia dunnii by next-generation sequencing technologies. The complete chloroplast genome sequence of Tainia dunnii is 158, 305 base pairs (bp) in length, including a pair of inverted repeat regions (IRs, 25, 244 bp), one large single-copy region (LSC, 86, 819 bp), one small single-copy region (SSC, 20, 998 bp). Besides, the complete chloroplast genome contains 136 genes in total, including 88 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed that Tainia dunnii has the closest relationship with Calanthe davidii and Calanthe triplicata . Our study lay a foundation for further research of Tainia dunnii .